1964
DOI: 10.1121/1.1919215
|View full text |Cite
|
Sign up to set email alerts
|

Lateralizing Effects of Interaural Phase Differences

Abstract: A discrepancy between experimental observation and theoretical construct is pointed out with reference to the lateralizing effects of interaural phase differences. In essence, the observation that a phase difference of 90 ø produces maximal sound lateralization appears less amenable to physiological explanation than a theoretical relationship in which lateralizing effect is proportional to the magnitude of interaural phase difference, at least up to an area of uncertainty near 180% N experiment by Garner and W… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

1974
1974
2016
2016

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 0 publications
1
5
0
Order By: Relevance
“…Our data obtained with pure tones agree with those reported by authors (e.g., Elpern and Naunton, 1964) who determined the interaural intensity difference required to offset a phase difference between signals. The results of this study also suggest that lateralization of high-frequency sinusoids is dependent solely on interaural intensity differences, whereas the lateralization of low-frequency tones is sensitive to interaural dispari-…”
Section: A Time-intensity Trading Functionssupporting
confidence: 94%
“…Our data obtained with pure tones agree with those reported by authors (e.g., Elpern and Naunton, 1964) who determined the interaural intensity difference required to offset a phase difference between signals. The results of this study also suggest that lateralization of high-frequency sinusoids is dependent solely on interaural intensity differences, whereas the lateralization of low-frequency tones is sensitive to interaural dispari-…”
Section: A Time-intensity Trading Functionssupporting
confidence: 94%
“…In this paper we have presented a model that obtains the random position variable/5 from simple operations on auditory-nerve activity, and we have compared its predictions to the results of various experimental studies. The model makes use of the description of auditory-nerve response and the display of interaural timing information presented in previous papers of this series (Colburn, 1973(Colburn, , 1977a The position-variable model also predicts the major results of centering studies by Elpern and Naunton (1964) and Young (1976) Fig. 2(a), is weighted by the product of twopulse-shaped functions, the distribution of the internal delays of the fiber pairs p(•), and the intensity function Lr(•').…”
Section: Discussion and Summarymentioning
confidence: 99%
“…Several studies have demonstrated a linear relationship between IPD and intracranial image location, independent of the frequency (<1200 Hz) (e.g. Sayers 1964; Elpern and Naunton 1964; Yost 1981). However, this relationship does not hold for IPDs beyond 90 ° where the intracranial image either moves towards the midline, jumps to the opposite side, or becomes perceptually diffuse, despite the increasing interaural delay (e.g.…”
Section: Methodsmentioning
confidence: 99%
“…However, this relationship does not hold for IPDs beyond 90 ° where the intracranial image either moves towards the midline, jumps to the opposite side, or becomes perceptually diffuse, despite the increasing interaural delay (e.g. Sayers 1964; Elpern and Naunton 1964; Domnitz and Colburn 1977; Shackleton et al 1991). Thus, one would expect both EEG and behavioural responses to demonstrate a link between behavioural and neural mechanisms of ITD processing.…”
Section: Methodsmentioning
confidence: 99%